Parental Engagement in Character Education for Generation Alpha in Diaspora: A Qualitative Study of Indonesian Families at Sekolah Indonesia Kuala Lumpur (SIKL), Malaysia - Handayani, Sri; Abd Majid, Mohamad Zuber; Wati, Andy Prasetyo; Hartanto, Wiwin; Dwiputri, Inayati Nuraini; Wahyuningsih, Dian (Global Educational Research Review, 2025)
Purpose –  This study addresses a critical gap in character education literature by examining how Indonesian parents in diaspora settings, specifically those with children attending Sekolah Indonesia Kuala Lumpur (SIKL), perceive and implement character education within the family. Given Generation Alpha’s deep immersion in technology and the shifting cultural identities of diaspora families, this research highlights the need for moral resilience fostered through family-based character development. Methods/Design/Approach – Using a qualitative approach, the study employed Focus Group Discussions (FGD) and in-depth interviews involving 30 purposively selected parents of SIKL students across grades X–XII. Data were collected through observation, semi-structured interviews, and document analysis, then thematically analyzed with the support of NVivo software. The analysis focused on six key dimensions of parental involvement: parenting, communication, home-based learning, contribution, decision-making, and collaboration. Findings – Parents consistently associated character education with empathy, honesty, religiosity, and emotional intelligence. Role modeling (35%), discussion and reflection (45%), and open communication emerged as dominant methods. Major challenges included children’s technology dependence (65%), limited parent–child time, and academic stress. Key support resources included family centers, faith communities, parenting groups, and social media networks. Originality/Value – This study offers novel insights into character education within transnational families, emphasizing the strategic role of parental engagement in preserving national identity and moral values in intercultural contexts. While exploratory, the study's findings serve as a theoretical and practical foundation for future research across diaspora settings. Practical Implications – Schools serving diaspora populations should institutionalize collaborative character education programs with active parental involvement. Family-centered training modules, value-based projects, and intercultural parenting forums are essential to maintain consistency in moral education. The study’s geographic and informant scope presents limitations, inviting future research to include student and teacher perspectives for a more holistic understanding. Keywords Character education, diaspora families, parental involvement, Generation Alpha, transnational education Paper type Research paper